Recuperable Traditions, Contemporary Voices - Kennedy, David (The Ekphrastic Encounter in Contemporary British Poetry and Elsewhere, 2012)
The American poet Adrienne Rich writes in 'In the Evening' that 'The old masters, the old sources, / haven't a clue what we're about' (Rich 1993: 287). Rich's poem dates from the mid-1960s and slightly predates the now well-established feminist project of recovering artistic and literary foremothers. This chapter begins by looking at some examples of ekphrastic poetry by earlier women poets and argues that such poetry as there is amounts to a recuperable tradition. A very interesting early example is Anne King's (1621-167?) 'Under Mr Hales Picture', not least because King had also made the picture she writes about, a black and white portrait drawing now lost. King's poem begins by registering the moment of its subject's death 'Even in that instant, when they had design'd / Tokeipe thee, by thy picture still in mind'. The poem has to do instead: 'the lines were figur'd by a woman's hand / Who had noe copy to be guided by / ButHales imprinted on her memory' (In Greer et al. 1988: 181). 'Noe copy' perhaps alludes to the female artist working outside established traditions of art or, at least, not basing her portrait on a preexistent model. There is no sense of separation between writer and subject here but, in contrast, a strong sense of intersubjectivity. King the artist and writer is formed by the internalized presence of her subject. Indeed, drawing on Ettinger, we can recreate an exemplary matrixial scene in which King looks at her own artistic creation and writes in response to it. Her gaze, which created the portrait drawing, now looks back at her. Her poem, then, registers the experience of recognizing oneself as part-object and partial subject. And this makes King's poem an example of the complex, many-layered ekphrastic encounter I argued for in Chapter 1.